How to draw and paint watercolors - Powell, Bill (California Walter foster publishing Inc, 1991)
covers all the Techniques uou need to know to creat beautiful watercolour paintings of people, landscapes, seascapes. still life children and animals
includes index
Includes bibliographical references
13
Keywords: Watercolor painting -- Technique